Perancangan Sitem Kompor Listrik dengan Fitur Pengaturan Suhu Otomatis untuk Meningkatkan Efesiensi Energi - Aldo Prima Aditia; Tata Sutabri (Router : Jurnal Teknik Informatika dan Terapan, 2024)
Efficient energy use in household appliances has become a primary concern as awareness of environmental sustainability grows. Smart electric stoves with automatic temperature control features offer an innovative solution to enhance energy efficiency while ensuring comfort and safety during use. This study aims to design and develop a smart electric stove system based on a microcontroller with automatic temperature control algorithms. The system employs temperature sensors to detect real-time temperature changes and a Proportional-Integral-Derivative (PID) algorithm to maintain stable temperatures as set by the user. A simple and intuitive user interface is designed to facilitate operation, while the automation feature allows the system to shut off the heating element independently when the temperature exceeds a safe threshold. Test results demonstrate that the designed system can reduce energy consumption by up to 25% compared to conventional electric stoves without automatic controls. Therefore, this research significantly contributes to the development of energy-efficient and safe smart kitchen appliances.